GUIDING Of The QURAN RECITATIONS In Al-MULIK SURA In A BOOK Of Al-HITIJAJ For RECITATIONS PARALLELED STUDY (Islamic Sciences Journal, 2023)
The study deals with the Quranic readings which mentioned in Almulk sura according to what the Arab scholars agreed about methods of Reading.The study focuses on eight books as sources of investigating (Kutub AlIhtijaj lil Kiraat starting from Ibn Khalaweih (passed a way 370 A.H), two books (Iarab Al Kiraat Assaba) and their explanations, as well as (Al huja fe Al kiraat Assaba). The study also deals with the last book which published by Abdullah Asherazi (died in 565 A.H) and it was called (Al Kitab Al Muwadhah fe Wujooh Al Kiraat and their explanations). The study tackles five methods of hew to read Quranic Uevses in a correct way, especially different readings in (Al Mulk Sura). The Arab scholars agreed about five methods of reading and it explains what referred by each of the Arab scholars and consequently the study focuses on the following points:1.Kutub Al Ihtijaj are different in explaining methods of reading of Quranic verses .The difference is shown clearly depending on prolixity and brevity.2.Maki Al Kaisi focused on predominance where he conceived two different methods of reading.
Keywords: The Arabic Language- hnguistics .Phonetics , Readings.